2018
DOI: 10.1111/jai.13698
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight and length-length relationships of eight fish species from river Ganga, India

Abstract: Summary Present study provides length–weight relationships (LWRs) and length–length relationships (LLRs) of eight fish species from river Ganga, India. Specimens were sampled from gill nets (mesh, 22–120 mm), cast nets (mesh, 12–14 mm), and seine nets (mesh, 12 mm) on quarterly basis from September 2016 to September 2017 within the river stretch from Buxar (25°33′43.90″N and 83°56′3.10″E) to Freserganj (21°35′40.58″N and 88°15′28.92″E). The b value ranged from 2.86 (Otolithoides pama) to 3.08 (Polynemus paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…LWRs can be used to convert length-frequency observations to biomass estimates while modelling an aquatic ecosystem (Kulbicki et al, 2005) and in converting length data obtained from back calculations on otoliths and scales. LWRs of other freshwater fishes from Indian rivers were previously reported by Baitha et al (2018), Borah et al (2018), Koushlesh et al (2018), Baitha et al (2017) and Nath et al (2017). The relative condition factor for L. calbasu, L. bata, L. rohita, L. dyocheilus and L. porcellus were estimated as 1.019± 0.023, 1.001 ±0.011, 1.013 ± 0.021, 1.005 ± 0.023 and 1.003 ±0.017, respectively (Table 2).…”
supporting
confidence: 57%
“…LWRs can be used to convert length-frequency observations to biomass estimates while modelling an aquatic ecosystem (Kulbicki et al, 2005) and in converting length data obtained from back calculations on otoliths and scales. LWRs of other freshwater fishes from Indian rivers were previously reported by Baitha et al (2018), Borah et al (2018), Koushlesh et al (2018), Baitha et al (2017) and Nath et al (2017). The relative condition factor for L. calbasu, L. bata, L. rohita, L. dyocheilus and L. porcellus were estimated as 1.019± 0.023, 1.001 ±0.011, 1.013 ± 0.021, 1.005 ± 0.023 and 1.003 ±0.017, respectively (Table 2).…”
supporting
confidence: 57%
“…For both the species, the LWRs were highly significant (p<0.01) and the coefficient of determination (r 2 ) values were 0.954 and 0.974 for O. pama and O. biauritus respectively. Baitha et al (2018) Nath et al (2004) and Hossain et al (2015). The observed differences in 'b' values may be due to the combination of one or more factors like habitat, area, seasonal effects, the degree of stomach fullness, gonad maturity, sex ratio, health condition, preservation techniques and length groups of studied specimens (Tesch, 1971).…”
Section: Length-weight Relationshipsmentioning
confidence: 99%
“…Hossain et al (2015) described the LWRs of Otolithoides biauritus and O. pama from the Tetulia River, southern Bangladesh. Recently Baitha et al (2018) reported the LWR of O. pama from Ganga River, India. All these studies were based on pooled samples.…”
Section: Introductionmentioning
confidence: 99%
“…The length–weight data also provide significant clues on changes in environment and fishery practices over a period of time (Dubey et al., 2012). In the recent years, a large number of studies were conducted on the LWRs of fish species from Ganga and Brahmaputra basins (Baitha, Karna, et al., 2018; Baitha, Sinha, et al., 2018; Borah et al., 2017; ; Karna et al., 2018; Koushlesh et al., 2018; Nath et al., 2019). Among major rivers of India, the Cauvery holds a unique status in harbouring high number of endemic fish species owing to the remarkable habitat heterogeneity throughout its course since a major part of the basin lies within the Western Ghats biodiversity hotspot.…”
Section: Introductionmentioning
confidence: 99%